Targeting the epidermal growth factor receptor (EGFR/ErbB) for the potential treatment of renal pathologies - Tawengi, Mohamed; Al-Dali, Yazan; Tawengi, Abdelaziz; Benter, Ibrahim F.; Akhtar, Saghir (Frontiers in Pharmacology, 2024)
Epidermal growth factor receptor (EGFR), which is referred to as ErbB1/HER1, is the prototype of the EGFR family of receptor tyrosine kinases which also comprises ErbB2 (Neu, HER2), ErbB3 (HER3), and ErbB4 (HER4). EGFR, along with other ErbBs, is expressed in the kidney tubules and is physiologically involved in nephrogenesis and tissue repair, mainly following acute kidney injury. However, its sustained activation is linked to several kidney pathologies, including diabetic nephropathy, hypertensive nephropathy, glomerulonephritis, chronic kidney disease, and renal fibrosis. This review aims to provide a summary of the recent findings regarding the consequences of EGFR activation in several key renal pathologies. We also discuss the potential interplay between EGFR and the reno-protective angiotensin-(1-7) (Ang-(1-7), a heptapeptide member of the renin-angiotensin-aldosterone system that counterregulates the actions of angiotensin II. Ang-(1-7)-mediated inhibition of EGFR transactivation might represent a potential mechanism of action for its renoprotection. Our review suggests that there is a significant body of evidence supporting the potential inhibition of EGFR/ErbB, and/or administration of Ang-(1-7), as potential novel therapeutic strategies in the treatment of renal pathologies. Thus, EGFR inhibitors such as Gefitinib and Erlinotib that have an acceptable safety profile and have been clinically used in cancer chemotherapy since their FDA approval in the early 2000s, might be considered for repurposing in the treatment of renal pathologies.